A New, Better BET: Rescuing and Revising Basic Emotion Theory - Hutto, Daniel D.; Robertson, Ian; Kirchhoff, Michael D. (Frontiers in Psychology, 2018)
Basic Emotion Theory, or BET, has dominated the affective sciences for decades (Ekman 1972, 1992, 1999; Ekman and Davidson 1994; Scarantino and Griffiths 2011). It has been highly influential, driving a number of empirical lines of research (e.g. in the context of facial expression detection, neuroimaging studies and evolutionary psychology). Nevertheless, BET has been criticized by philosophers, leading to calls for it to be jettisoned entirely (Colombetti 2014; Hufendiek 2016). This paper defuses those criticisms. In addition, it shows that we have good reason to retain BET. Finally, it reviews and puts to rest worries that BET’s commitment to affect programs renders it outmoded. We propose that, with minor adjustments, BET can be avoid such criticism when conceived under a radically enactive account of emotions. Thus, rather than leaving BET behind, we show how its basic ideas can be revised, refashioned and preserved. Hence, we conclude, our new BET is still a good bet.